Sistem Pakar Diagnosa Keluhan Selama Masa Nifas Dengan Metode Dempster Shafer - Wijayanti, Tita (LPPM Universitas Dinamika Bangsa, 2023)
The puerperium is a period after childbirth or can also be interpreted as a period of recovery in which the reproductive organs will undergo changes such as pre-pregnancy conditions by taking approximately 6 weeks. Nowadays, often the main focus for mothers and babies is on pregnancy and childbirth, while during the postpartum period a mother is also susceptible to diseases such as endometritis, metritis, mastitis, breast abscess, urinary tract infection, thromboplebitis, perineal wound infection, post SC wound infection, postpartum hemorrhage and baby blues which can get worse if not handled properly. The purpose of this study is to implement the Dempster Shafer method in an expert system application and test the accuracy of the system in identifying diseases that can attack during the postpartum period and provide treatment solutions from the diagnosis results. This expert system application produces outputs or diagnoses in the form of possible diseases suffered based on complaints or symptoms experienced by patients and displays the amount of confidence value in the disease obtained from calculations using Dempster Shafer. This system is tested using accuracy testing where a comparison is made between the results of the system diagnosis and the results of the expert diagnosis. The system accuracy rate in this study reached 93%, which shows a high level of reliability in providing the right diagnosis.Keywords: Postpartum Diseases, Expert System, Dempster Shafer